2004
DOI: 10.1161/01.cir.0000131942.77635.2d
|View full text |Cite
|
Sign up to set email alerts
|

Serum Total Homocysteine Concentrations and Risk of Stroke and Its Subtypes in Japanese

Abstract: Background-To date, no prospective studies have examined the association between serum homocysteine levels and the risk of stroke and stroke subtypes in Asian populations. Methods and Results-A prospective, nested, case-control study of Japanese subjects 40 to 85 years of age was conducted by using frozen serum samples from 11 846 participants in cardiovascular risk surveys collected from 1984 to 1995 for one community and 1989 to 1995 for the other two communities. By the end of 2000, we identified 150 incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
77
3
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 28 publications
(20 reference statements)
6
77
3
3
Order By: Relevance
“…The multivariate odds ratios of Hcy (after adjustment for body mass index, smoking, alcohol intake, hypertension, serum cholesterol, and other cardiovascular risk factors) were 2.99 for total stroke, 3.89 for ischemic stroke, 3.36 for lacunar infarction, and 1.63 for hemorrhagic stroke. 17 In our study no such effect was found -no correlation was observed between Hcy concentration and the development of CVA later on. Another prospective follow-up cohort study examined serum Hcy in relation to mortality and morbidity from coronary heart disease in 1,368 women.…”
Section: Discussioncontrasting
confidence: 73%
“…The multivariate odds ratios of Hcy (after adjustment for body mass index, smoking, alcohol intake, hypertension, serum cholesterol, and other cardiovascular risk factors) were 2.99 for total stroke, 3.89 for ischemic stroke, 3.36 for lacunar infarction, and 1.63 for hemorrhagic stroke. 17 In our study no such effect was found -no correlation was observed between Hcy concentration and the development of CVA later on. Another prospective follow-up cohort study examined serum Hcy in relation to mortality and morbidity from coronary heart disease in 1,368 women.…”
Section: Discussioncontrasting
confidence: 73%
“…There is conflicting evidence about the relationship of homocysteine and hemorrhagic stroke with some studies finding raised homocysteine levels in hemorrhagic stroke [23,24], others reporting the same in ischemic stroke [25], and still others finding raised homocysteine in both stroke subtypes [26]. Our finding of raised homocysteine concentrations in hemorrhagic stroke cases adds to the homocysteine-hemorrhagic stroke linkage.…”
Section: Discussionmentioning
confidence: 49%
“…[8][9][10] There is evidence from laboratory and clinical studies that elevated Homocysteine (eHcy), exerts direct toxic effects on both the vascular and nervous systems.…”
Section: Discussionmentioning
confidence: 99%